2017
DOI: 10.1007/s12041-017-0872-x
|View full text |Cite
|
Sign up to set email alerts
|

Illumina-based de novo transcriptome sequencing and analysis of Chinese forest musk deer

Abstract: The Chinese forest musk deer (Moschus berezovskii Flerov) is an endangered artiodactyl mammal. The musk secreted by sexually mature males is highly valued for alleged pharmaceutical properties and perfume manufacturing. However, the genomic and transcriptomic resources of musk deer remain deficiently represented and poorly understood. Next-generation sequencing technique is an efficient method for generating an enormous amount of sequence data that can represent a large number of genes and their expression lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Other studies have shown that testosterone plays an important role in the seasonal development of musk glands [92], and oxytocin may regulate the function of muskrat scented glands by the locally expressed receptors [94]. Studies based on transcriptome [42,43] and genetic analysis [35] have shown that a considerable number of genes involved in musk metabolism pathways, such as steroid biosynthesis, flavone and flavonol biosynthesis, terpenoid backbone biosynthesis, aldosterone-regulated sodium reabsorption was played a significant role in musk secretion. In this study, we identified 21 up-regulation DEGs which were closely associated with metabolism and response of steroid, terpenoid and hormone which were coincident with the previous reports [35,42,43].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other studies have shown that testosterone plays an important role in the seasonal development of musk glands [92], and oxytocin may regulate the function of muskrat scented glands by the locally expressed receptors [94]. Studies based on transcriptome [42,43] and genetic analysis [35] have shown that a considerable number of genes involved in musk metabolism pathways, such as steroid biosynthesis, flavone and flavonol biosynthesis, terpenoid backbone biosynthesis, aldosterone-regulated sodium reabsorption was played a significant role in musk secretion. In this study, we identified 21 up-regulation DEGs which were closely associated with metabolism and response of steroid, terpenoid and hormone which were coincident with the previous reports [35,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Studies based on transcriptome [42,43] and genetic analysis [35] have shown that a considerable number of genes involved in musk metabolism pathways, such as steroid biosynthesis, flavone and flavonol biosynthesis, terpenoid backbone biosynthesis, aldosterone-regulated sodium reabsorption was played a significant role in musk secretion. In this study, we identified 21 up-regulation DEGs which were closely associated with metabolism and response of steroid, terpenoid and hormone which were coincident with the previous reports [35,42,43]. Although there have been several studies on the secretion of musk, the genetic mechanisms of musk secretion are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations